Experimental determination and numerical simulation of material and damage behaviour of 3D printed polyamide 12 under cyclic loading. (15th April 2020) - Schob, Daniela; Sagradov, Ilja; Roszak, Robert; Sparr, Holger; Franke, Rainer; Ziegenhorn, Matthias; Kupsch, Andreas; Léonard, Fabien; Müller, Bernd R.; Bruno, Giovanni
Highlights: 3D printed polyamide 12 shows pores and inhomogeneous material structure. The pore shape changes due to cyclic loading, voids become more spherical. Chaboche material model can simulate the material behaviour of 3d printed polyamide. Coupling of Chaboche and GTN models enables the simulation of the damage behaviour. Abstract: The material and damage behaviour of additively manufactured polyamide 12 under cyclic loading was characterized by cyclic tests and microstructure analysis by using microscopy, X-ray refraction, and computed tomography. The results were used to determine parameters for the viscoplastic material model by Chaboche and a damage model by Gurson-Tvergaard-Needleman. The temperature was monitored during the experiments and the self-heating effect was observed. By including this effect, a higher accuracy could be achieved with the results of mechanical experiments.